2014
DOI: 10.1186/1471-2164-15-767
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms generated by genotyping by sequencing to characterize genome-wide diversity, linkage disequilibrium, and selective sweeps in cultivated watermelon

Abstract: BackgroundA large single nucleotide polymorphism (SNP) dataset was used to analyze genome-wide diversity in a diverse collection of watermelon cultivars representing globally cultivated, watermelon genetic diversity. The marker density required for conducting successful association mapping depends on the extent of linkage disequilibrium (LD) within a population. Use of genotyping by sequencing reveals large numbers of SNPs that in turn generate opportunities in genome-wide association mapping and marker-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 54 publications
2
48
0
1
Order By: Relevance
“…The number of SNPs per chromosome varied according to chromosome with the least on chromosome 10 (416 SNPs; 3%) and the most on chromosome 2 (2561 SNPs; 16%); the average was 1487 SNPs (Figure 1). Similar distributions have been detected in the germplasm of different crops using SNPs, including maize (Romay et al, 2013), chickpea (Bajaj et al, 2014), and watermelon (Nimmakayala et al, 2014). Schröder et al (2016), reported that the most SNPs were located on chromosome 8 using ApeKI and MseI/ TaqαI restriction enzymes.…”
Section: Snp Discovery By Dartseqmentioning
confidence: 69%
See 1 more Smart Citation
“…The number of SNPs per chromosome varied according to chromosome with the least on chromosome 10 (416 SNPs; 3%) and the most on chromosome 2 (2561 SNPs; 16%); the average was 1487 SNPs (Figure 1). Similar distributions have been detected in the germplasm of different crops using SNPs, including maize (Romay et al, 2013), chickpea (Bajaj et al, 2014), and watermelon (Nimmakayala et al, 2014). Schröder et al (2016), reported that the most SNPs were located on chromosome 8 using ApeKI and MseI/ TaqαI restriction enzymes.…”
Section: Snp Discovery By Dartseqmentioning
confidence: 69%
“…This SNP number was similar to other diversity studies. For example, Jarquín et al (2014) detected 52,349 SNPs and after filtering used 16,502 SNPs obtained from 301 elite soybean breeding lines, and Nimmakayala et al (2014) detected 23,693 SNPs and after filtering used 11,485 in a genetic analysis of watermelon germplasm. Likewise, Phuong Phung et al (2014) characterized 182 rice accessions with 25,971 markers after a data-cleaning step.…”
Section: Snp Discovery By Dartseqmentioning
confidence: 99%
“…have been estimated by different approaches, including the use of biochemical, morphological and molecular markers [1115]. Molecular markers permit in-depth characterization of germplasm [16] and improve the efficiency and precision of conventional plant breeding schemes through marked-assisted selection. Amplified Fragment Length Polymorphism (AFLP), Simple Sequence Repeat (SSR) and Single Nucleotide Polymorphism (SNP) markers proved useful in detecting genetic diversity and determining genetic relationships in pepper germplasm [1315].…”
Section: Introductionmentioning
confidence: 99%
“…SNPs generated by GBS have been successfully deployed for genetic diversity analysis and Genome-wide association studies (GWAS) in several crops (Poland and Rife, 2012; Narum et al, 2013; Liu et al, 2014; Nimmakayala et al, 2014, 2016; Guajardo et al, 2015; Otto et al, 2016). Increased marker density across the chromosomes facilitates to estimate genome-wide non-random association of allelic states across the chromosomes, which is known as Linkage disequilibrium (LD; Mackay and Powell, 2007; Reddy et al, 2014; Baird, 2015; Wang et al, 2015; Zanke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%